A unique Kelch domain phosphatase in Plasmodium regulates ookinete morphology, motility and invasion. - Nisha Philip; Heli J Vaikkinen; Laurence Tetley; Andrew P Waters (PLoS ONE)
Signalling through post-translational modification (PTM) of proteins is a process central to cell homeostasis, development and responses to external stimuli. The best characterised PTM is protein phosphorylation which is reversibly catalysed at specific residues through the action of protein kinases (addition) and phosphatases (removal). Here, we report characterisation of an orphan protein phosphatase that possesses a domain architecture previously only described in Plantae. Through gene disruption and the production of active site mutants, the enzymatically active Protein Phosphatase containing Kelch-Like domains (PPKL, PBANKA_132950) is shown to play an essential role in the development of an infectious ookinete. PPKL is produced in schizonts and female gametocytes, is maternally inherited where its absence leads to the development of a malformed, immotile, non-infectious ookinete with an extended apical protrusion. The distribution of PPKL includes focussed localization at the ookinete apical tip implying a link between its activity and the correct deployment of the apical complex and microtubule cytoskeleton. Unlike wild type parasites, ppkl(-) ookinetes do not have a pronounced apical distribution of their micronemes yet secretion of microneme cargo is unaffected in the mutant implying that release of microneme cargo is either highly efficient at the malformed apical prominence or secretion may also occur from other points of the parasite, possibly the pellicular pores.